Negative prompts aimed at maintaining eating independence. (November 2019) - Palese, Alvisa; Gonella, Silvia; Kasa, Tea; Caruzzo, Davide; Hayter, Mark; Watson, Roger
Background: Psychological abuse of older people is difficult to recognise; specifically, nursing home residents have been documented to be at higher risk of psychological abuse during daily care, such as during feeding. Healthcare professionals adopt positive and negative verbal prompts to maintain residents' eating independence; however, negative prompts' purposes and implications have never been discussed to date. Research aims: To critically analyse negative verbal prompts given during mealtimes as forms of abuse of older individuals and violation of ethical principles. Research design: This is a secondary analysis of three cases of negative prompts that emerged in a large descriptive study based upon focus group methodology and involving 13 nursing homes and 54 healthcare professionals. Participants and research context: This study included 3 out of 13 nursing homes caring for residents with moderate/severe functional dependence in self-feeding mainly due to dementia; in these nursing homes, we conducted three focus groups and 13 healthcare professionals participated. Ethical considerations: This study was conducted in accordance with the Human Subject Research Ethics Committee guidelines after being approved by the Review Board of the Trust. Findings: With the intent of maintaining self-feeding independence, negative verbal prompts have been reported as being used by nursing home teams. By critically analysing these negative prompts, it turned out they could trigger intimidation, depression and anxiety and thus could be considered as forms of abuse; moreover, negative prompts can threaten the ethical principles of (1) autonomy using a paternalist approach, (2) beneficence and non-maleficence as with the intent to act in the best interests of residents (to maintain self-feeding independence) they are harmed in their dignity and (3) justice, given that residents who received negative prompts are treated differently from those who received positive prompts. Discussion: Eating should be a pleasant experience with a positive impact on physiological, psychological and social well-being. However, negative prompting can lead to abuse and violation of basic ethical principles, destroying the healthcare professional resident and relative relationships strongly dependent on trust. Conclusion: Negative verbal prompting must be avoided.